Structure of the pelvic and penile urethra - Relationship with the ducts of the sex accessory glands of the Mongolian gerbil (Meriones unguiculatus) - Pinheiro, Patricia Fernanda Felipe [UNESP]; Almeida, C. C D [UNESP]; Segatelli, T. M. [UNESP]; Martinez, M.; Padovani, C. R. [UNESP]; Martinez, F. E. [UNESP] (Wiley, 2003)
The urethra is the main place of entry for sexually transmitted pathogens. However, there is little literature on the morphology of the urogenital system, principally the urethra and ducts of the sex accessory glands. The Mongolian gerbil is an insectivorous, herbivorous and monogamous rodent with nocturnal habits; it has been used successfully as a laboratory animal since the 1960s. Therefore, the objective of the present paper was to describe the structure and ultrastructure of the urethra and its relations to the ducts of the accessory sex glands of the Mongolian gerbil (Meriones unguiculatus), contributing to the understanding of the reproductive biology of the rodent and aiming to provide data for future experimental studies. Conventional techniques of light and scanning electron microscopy were utilized. The urethra and ducts of the accessory sex glands are similar to those of the albino rat and the mouse. However, there is variation in drainage type among accessory sex glands for the inner urethra. The ducts of the seminal vesicle, the ductus deferens, drain their contents independently into the ampullary duct that opens in the urethra. The ducts of the prostate, coagulating and bulbourethral glands drain their contents independently into the urethra.
Keywords: Male urogenital system; Morphology; Rodents; accessory sex gland; albinism; animal tissue; bulbourethral gland; controlled study; flow kinetics; gerbil; male; microscopy; mouse; nonhuman; penis; priority journal; prostate; rat; reproduction; rodent; scanning electron microscopy; seminal vesicle; tissue structure; ultrastructure; urethra; urogenital system; vas deferens; Animals; Bulbourethral Glands; Genitalia, Male; Gerbillinae; Male; Microscopy, Electron, Scanning; Penis; Prostate; Urethra; Vas Deferens; Animalia; Meriones; Meriones unguiculatus; Rodentia